Visible-light-mediated flow protocol for Achmatowicz rearrangement - Oja, Joachyutharayalu; Kumar, Sanjeev; Pabbaraja, Srihari (Beilstein Journal of Organic Chemistry, 2024)
The batch processes of APIs/pharmaceutical synthesis are prone to suffer significant limitations, including longer process time, shortage of skilled manpower, laborious post-synthetic work-up, etc. To address the inherent limitations of batch processes, a novel approach was undertaken, resulting in the establishment and development of a visible light-assisted modular photo-flow reactor with a seamlessly integrated post-synthetic work-up procedure enabling the efficient synthesis of dihydropyranones from furfuryl alcohols. The reaction uses sun light as green energy source, and the novel photo-flow reactor platform developed with an integrated system enabling a downstream process in a time and labor-efficient manner which facilitates the Achmatowicz rearrangement, resulting in a fast (10 min) formation of the dihydropyranone products.
Keywords: Achmatowicz reaction; flow chemistry; furfuryl alcohols; photocatalyst; sunlight